Saṃgrāma, saṃgaṭhana, byaktitva - Hosena, Nājira, 1930- (Ājāda Musalima Klāba : paribeśaka, Jātīẏa Grantha Kendra, 1983)
History of the Azad Muslim Club, 1945-1983; a Dacca-based social welfare organization.